Adapting agricultural water governance to climate change: experience from Germany, Spain and California - Insa Theesfeld; Oscar Schmidt; Waltina Scheumann; Elke Herrfahrdt-Pähle; Chinwe Ifejika Speranza (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
This study describes and discusses initiatives taken by public (water) agencies in the state of Brandenburg in Germany, the state of California in the USA and the Ebro River Basin in Spain in response to the challenges which climate change poses for the agricultural water sector. The drivers and actors and the process of changing agricultural water governance are its particular focus. The assumptions discussed are: (i) the degree of planned and anticipatory top-down implementation processes decreases if actions are more decentralized and are introduced at the regional and local level; (ii) the degree of autonomous and responsive adaptation approaches seems to grow with actions at a lower administrative level. Looking at processes of institutional change, a variety of drivers and actors are at work such as changing perceptions of predicted climate impacts; international obligations which force politicians to take action; socio-economic concerns such as the cost of not taking action; the economic interests of the private sector. Drivers are manifold and often interact and, in many cases, reforms in the sector are driven by and associated with larger reform agendas. The results of the study may serve as a starting point in assisting water agencies in developing countries with the elaboration of coping strategies for tackling climate change-induced risks related to agricultural water management.
Keywords: 330